Expanding the spectral response of a dye-sensitized solar cell by applying a selective positioning method - Park, Se Woong; Lee, Kyungtae; Lee, Doh-Kwon; Ko, Min Jae; Park, Nam-Gyu; Kim, Kyungkon (IOP PUBLISHING LTD, 2011)
We have developed a facile method to position different dyes (N719 and N749) sequentially in a mesoporous TiO2 layer through selective desorption and adsorption processes. From the selective removal of the only upper part of the first adsorbed dye, double-layered dye-sensitized solar cells have been successfully achieved without any damage to the dye. From the incident photon-to-current conversion efficiency (IPCE) measurement, the multi-layered dye-sensitized solar cell (MDSSC) was found to exhibit an expanded spectral response for the solar spectrum while maintaining the maximum IPCE value of each single-layered cell. The highest photocurrent density, 19.3 mA cm(-2), was obtained from the MDSSC utilizing an N719/N749 bi-layered mesoporous TiO2 film. The power conversion efficiency of 9.8% was achieved from the MDSSC, which is higher than that of single N719-or N749-based cells and cocktail-dyed (a mixture of N719 and N749) cells.
Keywords: CONVERSION EFFICIENCY; ORGANIC-DYES; TIO2